2011
DOI: 10.2166/wst.2011.316
|View full text |Cite
|
Sign up to set email alerts
|

Solar disinfection for the post-treatment of greywater by means of a continuous flow reactor

Abstract: SODIS (solar disinfection) is a low-cost alternative for water decontamination. The method is based on the exposure of water, contained in PET bottles, to direct sunlight, and mainly its UV-A and infrared components. The present research studied SODIS as a low cost alternative for the inactivation of Escherichia coli (E. coli) in treated greywater, aiming at its reuse for more noble applications. Experiments were performed in (i) batch mode (2 L PET-bottles), testing the effect of turbidity on system efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Despite the concerns raised about the effective inactivation achievable in recirculation and high flow rate SODIS reactors an application may still be possible in the (pre-) treatment of grey water. Pansonato et al have reported 2 log reductions in E. coli levels using a 51 L continuous pilot-scale reactor prototype using grey water [113].…”
Section: Flow Reactorsmentioning
confidence: 99%
“…Despite the concerns raised about the effective inactivation achievable in recirculation and high flow rate SODIS reactors an application may still be possible in the (pre-) treatment of grey water. Pansonato et al have reported 2 log reductions in E. coli levels using a 51 L continuous pilot-scale reactor prototype using grey water [113].…”
Section: Flow Reactorsmentioning
confidence: 99%
“…Post exposure regrowth possibilities are minimised by consuming the solar disinfected water in a period less than 24 hours post exposure (McGuigan et al, 2012). Black painted solar water disinfection containers, placing the SODIS reactors on reflective surface and filtering the turbid water prior to filling into the reactor (Pansonato et al, 2011) are some advances made to enhance solar water disinfection efficiency.…”
Section: Solar Energy Use In Water Disinfection Proceduresmentioning
confidence: 99%
“…In general, a graywater treatment system is designed to carry out four processes, viz., sedimentation, filtration, biological treatment, and disinfection. A range of novel approaches, such as improved zeolite filters, solar disinfection, and membrane bioreactors, are gaining momentum in the field of graywater treatment (Widiastuti et al 2011;Pansonato et al 2011;Hu, et al 2011). Zeolite is a material that promotes cation exchange and is highly sensitive to contaminants in graywater such as heavy metals and ammonium ions.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Using natural zeolite filters of different origin, Widiastuti et al (2011) achieved a reduction in ammonium of up to 97%. Disinfection of graywater by using solar ultraviolet-A (long-wave) to inactivate E. coli has been found to be economical in regard to the operating costs of treatment systems (Pansonato et al 2011). In addition, membrane bioreactors can help by yielding marked reduction in the turbidity and BOD 5 of graywater (Hu, et al 2011).…”
Section: Treatment Optionsmentioning
confidence: 99%